KERAGAMAN FAMILI ARECACEAE DI TAMAN NASIONAL WAY KAMBAS SEBAGAI SUMBER BELAJAR KURIKULUM MERDEKA - Prasetyo, Idar Yongky; Zen, Suharno; Pratiwi, Dasrieny (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This research aims to (1) determine the plant species of the Arecaceae family in the forest area of the Way Kambas SPTN II Bungur National Park (Resort Toto Projo) East Lampung Regency, (2) determine the plant diversity index of the Arecaceae family in the forest area of the Way Kambas SPTN II Bungur National Park (Resort Toto Projo) East Lampung Regency, (3) Find out whether the results of the research are suitable or not to be used as a Biology learning resource in the form of Student Worksheets based on Discovery Learning. The type of research used was descriptive qualitative, with a purposive sampling method combined with line transects. The results found from this research were 15 species from 294 individuals. The results of the overall calculation of the diversity index for the Arecaceae family in the Way Kambas SPTN II Bungur National Park Forest Area (Toto Projo Resort) show a figure of 2.4871, including the medium category. Validation of learning resources is carried out by 5 validators including material expert validation, design validation, and language validation. The validation results from material experts got a score of 81%, validation from design experts got a score of 82%, and validation from language experts got a score of 78%. The feasibility of the Student Worksheets based on Discovery Learning product that was created obtained an average score from all validators, namely 80%, namely with good criteria, and was declared valid and suitable as a student learning resource.